Chimeric Antigen Receptor T-Cells: New Approaches to Improve Their Efficacy and Reduce Toxicity. Issue 6 (November 2015) - Maus, Marcela V.; Powell, Daniel J.
Abstract : Abstract: The durable remission of B-cell leukemia and lymphoma following chimeric antigen receptor (CAR) T-cell therapy has brought this new form of adoptive immunotherapy to center stage with the expectation that CAR T-cell therapy may provide similar efficacy in other hematologic and solid cancers. Herein, we review recent advances in the areas of CAR design that improve CAR T-cell proliferation, engraftment, and efficacy, as well as clinical application strategies that are designed to improve clinical efficacy while reducing the risk of toxicity and broaden patient access to this promising form of cancer immunotherapy.